Syntax Mastery among Adult Learners through the Mistake Buster Technique - Framesthia, Luthfi Mustika; Abdurahman, Maman; Saleh, Nalahuddin; Siregar, Fadhilah Ramadhani (Mantiqu Tayr: Journal of Arabic Language, 2025)
The importance of mastering Arabic syntax for Muslims makes this field widely sought after, not only among young learners but also among adults. However, innovations in Arabic syntax instruction tailored to the needs of adult learners are still rarely developed. This study aims to describe the application of an inductive-based technique, namely Mistake Buster, in teaching Arabic syntax, particularly the structure of jumlah fi‘liyyah. The study uses a qualitative method with a case study approach involving five adult female learners over the age of 20 in a semi-private Naḥwu Class program. The results show that adult learners not only better understand the structure of jumlah fi‘liyyah but also gain a deeper understanding of i‘rāb. Learners also better understand types of kalimah and their differences; recognize the kinds, meanings, and patterns of jumlah; understand the appropriate use of ṣifah in fā’il or maf‘ūl bih; and are able to analyze elements such as fi‘il, fā’il, maf‘ūl bih, ḥarf, isim majrūr, and ṣifah in a jumlah, along with their i‘rāb signs. In addition, their activeness, curiosity, self-confidence, critical thinking, memory, and motivation improve. This study contributes significantly to Arabic syntax instruction for adult learners and recommends developing instructional materials or media based on the Mistake Buster technique.